Analisis Waktu Pemprosesan Layanan Enterprise PT. Telkomsat Menggunakan Metode Regresi Linear Berganda - Taufik, Andi; Muslimin, Putra (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
This study aims to analyze the influence of technical and non-technical factors on the company’s service processing duration. The research data were obtained from the company’s historical service records with independent technical variables consisting of Carrier-to-Noise Ratio (CNR), Signal Quality Factor (SQF), Customer Priority Index (CPI), and Latency, as well as non-technical variables including weather conditions and location distance. The analysis method applied in this study is multiple linear regression with a quantitative approach. The simultaneous test results (F-test) indicated that all independent variables collectively exert a significant effect on service processing duration. However, the partial test results (t-test) specifically proved that only weather and location distance variables have a significant effect p < 0,05, while the technical factors do not contribute a significant influence independently. The regression model developed yields an Adjusted R² value of 0.868, indicating that 86.8% of the variation in service processing duration can be explained by the studied independent variables. Furthermore, the model evaluation demonstrates a low prediction error rate, with a Mean Absolute Percentage Error (MAPE) value of 10.6%. These findings conclude that non-technical or external factors hold a more dominant role in determining the efficiency of service processing time compared to the company’s internal technical factors